Empowering Workplace Safety Culture through the Design and Implementation of a Safety Talk SOP in Railway HSE Practices - Gustiawan, Willson; Dayoh, Abhinaya Augusto; Wirda, Fisla (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2025)
Purpose This community service was initiated to address the lack of standardization and limited engagement in the implementation of Safety Talk sessions at PT Kereta Api Indonesia (Persero) Divre II West Sumatera. Despite being conducted regularly, these HSE communication activities lacked clear structure, facilitator guidance, and evaluation mechanisms, which hindered their effectiveness in fostering a preventive safety culture. Methods - The activity adopted a participatory and qualitative approach, involving field observation during a student internship, stakeholder interviews, and collaborative intervention design. Key stages included needs assessment, SOP drafting, facilitator training design, internal coaching sessions, and validation. Result and Discussions - The intervention successfully produced a structured Standard Operating Procedure (SOP) tailored to the organization’s Safety Talk program, alongside a facilitator training module to enhance communication skills and session delivery. Internal coaching sessions validated the practicality of both tools, leading to increased engagement and positive feedback from participants. The program documentation was formally handed over to the organization as part of the knowledge transfer process. Conclusion - The integration of SOP and facilitator training transformed Safety Talk from a routine obligation into a strategic platform for HSE awareness and behavioral change. To sustain impact, continuous monitoring, institutional support, and regular capacity building are recommended. This model offers a replicable framework for strengthening HSE communication in other high-risk industries.